Paranasal Sinuses - Singh Gendeh, Balwant (IntechOpen, 2017)
This book emphasizes on five different sections of rhinology, namely, 'Surgical Anatomy', 'Dental-Related Diseases', 'Radiological Imaging', 'Nasal Spaces' and 'Surgical Training'. It incorporates new clinical and research developments as well as future perspectives in the ever-expanding field of rhinology. I dedicate this book to those of you who pick up the torch and by continued research, close clinical observation and the high quality of clinical care as well as publication and selfless teaching, further advance knowledge in rhinology from this point forward. This is intended to be a guide for other books to follow. General otolaryngologist, rhinologist, researchers, specialists, trainees and general practitioners with interest in otolaryngology will find this book useful and interesting.